Evapotranspiration and biomass modelling in the Pontal Sul Irrigation Scheme - Araujo, Leandro Moscôso [UNESP]; Teixeira, Antônio Heriberto de Castro [UNESP]; Bassoi, Luís Henrique [UNESP] (Taylor & Francis, 2020)
In order to make feasible the use of irrigated areas of the Pontal Sul Irrigation Scheme in Petrolina, State of Pernambuco, Brazil, modelling of real evapotranspiration (ET) and plant biomass production (BIO) at a large scale was performed with associated agro-meteorological data and the algorithm SAFER (Simple Algorithm For Evapotranspiration Retrieving) using MODIS images for the years 2010–2017. The year 2012 presented the highest ET average with 3.15 mm day−1 in the rainy season, reaching a maximum of 6 mm day−1. The lowest mean ET was recorded in the year 2013, with 0.08 mm day−1 in the dry season, and the maximum recorded for the period was 3.40 mm day−1 in the irrigated agricultural area. For BIO, the highest average was 104.82 kg ha−1 day−1, during the rainy season of 2012, reaching a maximum value of 252 kg ha−1 day−1. The lowest average was for the dry period of 2013, with a value of 0.93 kg ha−1 day−1, and a maximum of 112.51 kg ha−1 day−1 in the irrigated agricultural area. The higher ET results represent moisture in the root zone, provided by rainfall and/or irrigation, showing maximum values in the rainy season. The results obtained for BIO suffer greatly from perimeter water availability. The present study becomes very important to the management of water resources, as it provides an increase in water productivity for food production.